Biochar efficiency in pesticides sorption as a function of production variablesâa review - Yavari, S. (Springer Verlag, 2015)
Biochar is a stabilized, carbon-rich by-product derived from pyrolysis of biomass. Recently, biochar has received extensive attentions because of its multi-functionality for agricultural and environmental applications. Biochar can contribute to sequestration of atmosphere carbon, improvement of soils quality, and mitigation of environmental contaminations. The capability of biochar for specific application is determined by its properties which are predominantly controlled by source material and pyrolysis route variables. The biochar sorption potential is a function of its surface area, pores volume, ash contents, and functional groups. The impacts of each production factors on these characteristics of biochar need to be well-understood to design efficient biochars for pesticides removal. The effects of biomass type on biochar sorptive properties are determined by relative amounts of its lingo-cellulosic compounds, minerals content, particles size, and structure. The highest treatment temperature is the most effective pyrolysis factor in the determination of biochar sorption behavior. The expansion of micro-porosity and surface area and also increase of biochar organic carbon content and hydrophobicity mostly happen by pyrolysis peak temperature rise. These changes make biochar suitable for immobilization of organic contaminants. Heating rate, gas pressure, and reaction retention time after the pyrolysis temperatures are sequentially important pyrolysis variables effective on biochar sorptive properties. This review compiles the available knowledge about the impacts of production variables on biochars sorptive properties and discusses the aging process as the main factor in post-pyrolysis alterations of biochars sorption capacity. The drawbacks of biochar application in the environment are summarized as well in the last section. Â© 2015, Springer-Verlag Berlin Heidelberg.